Freud's metapsychology of sublimation - Campos, Érico Bruno Viana [UNESP]; Loffredo, Ana Maria (My University, 2019)
This theoretical essay aimed to present the metapsychology of the concept of sublimation in Freud's work. The interest is justified by the fact that this is one of the broadest and least elaborated concepts in Freudian theory, and its last formulations were particularly little explored in later developments in most schools of psychoanalysis. In this sense, the Freudian discourses on sublimation, centered on the transformations of the goal and the object of satisfaction, will be characterized. Two moments are defended: one in the context of the first drive dualism, in which the sublimation concerns the desexualization, another in the second dualism, in which the sublimation articulates with the erotization of the death drive, through narcissistic identifications. It is proposed that they be perceived as distinct moments of a general process, in terms of a primary and secondary sublimation. In conclusion, we discussed the implications of this last discourse for understanding the relation between desire and culture, as well as for the psychoanalytic view of man.
A metapsicologia freudiana da sublimação
Keywords: Freud; Psychoanalysis and culture; Sigmund (1856-1939); Sublimation